How do hospitals sustain delivery of health care in conditions of protracted armed conflict? A case study of the Hospital San Andrés ESE in Tumaco, Colombia - Diaz Velasquez, Diego Mauricio (The University of Edinburgh, 2023)
BACKGROUND: Colombia, a middle-income country in Latin America, has experienced a protracted armed conflict for six decades, driven predominantly by the drug trade. The municipality of Tumaco, a port city located in the Southwest province of Nariño, has experienced the highest intensity of conflict in recent years. In Tumaco, the conflict has created significant challenges for the operation of key social services particularly its main hospital, Hospital San Andrés ESE, a government-owned but operationally autonomous facility. While the hospital experiences significant challenges owing to the conflict, it has continued to provide health services. At the global level, there is limited evidence on how hospitals continue to address population health needs in conflict-affected settings. Therefore, little is known about the challenges these facilities face, the strategies employed to face the challenges, or the support they receive or need. This thesis seeks to examine these neglected issues through a qualitative case study of the Hospital San Andrés ESE. AIM AND OBJECTIVES: This research focuses on understanding how hospitals sustain delivery of health care to populations in conditions of protracted armed conflict through an in-depth analysis of one hospital system: the Hospital San Andes ESE in Tumaco, Colombia. To achieve this aim, the research investigates: (i) the challenges the hospital faces to continue its operations in the conflict-affected environment, (ii) how the hospital responds to such challenges to sustain health care delivery; (iii) determine from research participants what needs to improve with the hospital response to challenges, so the hospital can better address the population health needs. METHODS: This project uses a qualitative case study approach drawing on data from 48 semi-structured interviews with hospital personnel and a range of policy actors around the hospital system which provide financial or in-kind support to the facility. Similarly, the study examines documents produced by key policy stakeholders and commentators (government authorities, the hospital, research centres, NGOs, humanitarian actors and local media). Collection and thematic analysis of the data were guided by the “everyday resilience” framework, which embeds the analysis of conflict-related challenges in the context of wider resource constraints. RESULTS: The results were organised to respond to the research objectives directly, addressing (i) the challenges the hospital faces in the conflict setting, (ii) how the hospital responds to such challenges; (iii) determining what needs to improve with the hospital response to challenges. The results highlight the combination of conflict-related and routine challenges faced by the Hospital San Andrés ESE, such that the sudden shocks and disruptions to hospital activities generated by the conflict (e.g., due to death threats to personnel, disruption of supply chains, and damage to infrastructure) take place in an operational context burdened by financial constraints, infrastructure obsolescence, and managerial dysfunction. These conflict and routine challenges interact, creating a particularly difficult operating environment for the delivery of health services. This study recognised the hospital employs 6 responses to address challenges: 1) Activation of emergency systems whereby the hospital joins forces with government security bodies to discuss challenges and find ways to address them. 2) Hospital managers plan and monitor threatened hospital functions and work internally or in negotiation with commercial parties to address challenges. 3) Activation of support networks where the hospital obtains or receives financial or in-kind support from private, non-government, and health system actors. 4) The hospital collaborates with voluntary groups who are citizens freely gathered to monitor hospital performance and seek solutions to problems. 5) The central government intervenes in hospital activities where the facility rescinds its autonomy to enhance administrative decision-making and allocation of resources, and 6) the hospital structures investment projects which involves the design and presentation of grants to government authorities to attain funding and manage operational problems. While these arrangements provide significant support for the hospital to sustain service delivery, further investment to strengthen these is needed. CONCLUDING DISCUSSION. Hospitals operating in conflict settings face a combination of conflict and routine challenges that require tailored support arrangements to function adequately. Otherwise, desirable organisational forms – e.g., managerial, and financial autonomy – may not be meaningful or helpful in such circumstances, and additional central government oversight, as well as financial and in-kind support, may be required. To sustain services, hospitals also require skilful managers to recognise and mitigate challenges along with the nurture and expansion of support networks with third parties within or outside the health system.
Keywords: Hospitals; Heath system Resilience; Armed Conflict